The Antipsychotic Effects of Omega-3 Fatty Acids in Rats. (September 2015) - Kokacya, Mehmet Hanifi; Inanir, Sema; Copoglu, Umit Sertan; Dokuyucu, Recep; Erbas, Oytun
Abstract: Background: In humans, omega-3 fatty acids are necessary for cell membranes, brain function and nerve transmission continuation. When animals are exposed to a new environment—or as a result of an apomorphine application that creates an agonistic effect on D1 and D2 receptors—they display behavioral reactions like rearing and stereotypy. This study aims to reveal the possible antipsychotic and oxidative effects of omega-3 fatty acids by comparing with chlorpromazine, a conventional antipsychotic drug, through evaluating the novelty-induced rearing and apomorphine-induced stereotypic behaviors, as well as malondialdehyde and glutathione levels in rats. Methods: Twenty-eight, adult, male, Wistar rats were used in the study. Briefly, 4 groups of rats (n = 7) were administered docosahexaenoic acid (DHA) + eicosapentaenoic acid (EPA) (300 mg/kg; DHA: 120 mg/kg + EPA: 180 mg/kg intraperitoneally [IP]), DHA + EPA (150 mg/kg; DHA: 60 mg/kg + EPA: 90 mg/kg IP), chlorpromazine (1 mg/kg, IP) and isotonic saline (1 mL/kg, IP). One hour later, apomorphine (2 mg/kg, subcutaneously) was administered to each rat. After the apomorphine administration, rats were observed for stereotypic behavior. Results: This study shows that omega-3 fatty acids, "similar to antipsychotics, " reversed the psychotic like effects, increase of oxidants and decrease of antioxidants that are composed experimentally in rats. Conclusions: The application of omega-3 fatty acids has antipsychotic effects and causes an oxidative imbalance. This study adds new evidence to the current literature regarding the possible antipsychotic effects of omega-3 fatty acids.